Can civilian attitudes predict insurgent violence? Ideology and insurgent tactical choice in civil war. (January 2017) - Hirose, Kentaro; Imai, Kosuke; Lyall, Jason
Are civilian attitudes a useful predictor of patterns of violence in civil wars? A prominent debate has emerged among scholars and practitioners about the importance of winning civilian 'hearts and minds' for influencing their wartime behavior. We argue that such efforts may have a dark side: insurgents can use pro-counterinsurgent attitudes as cues to select their targets and tactics. We conduct an original survey experiment in 204 Afghan villages and establish a positive association between pro-International Security Assistance Force attitudes and future Taliban attacks. We extend our analysis to 14, 606 non-surveyed villages and demonstrate that our measure of civilian attitudes improves out-of-sample predictive performance by 20–30% over a standard forecasting model. The results are especially strong for Taliban attacks with improvised explosive devices. These improvements in predictive power remain even after adjusting for possible confounders, including past violence, military bases, and development aid.